2016
DOI: 10.5152/tud.2016.78972
|View full text |Cite
|
Sign up to set email alerts
|

Rarely seen complications of circumcision, and their management

Abstract: Circumcisions performed by untrained individuals are to be blamed for the complications of circumcision reported in this country. The rate of complications increases during the "circumcision feasts" where multiple circumcisions were performed. This also predisposes to transmission of various diseases, primarily hepatitis B/C and AIDS. Circumcision is a surgical procedure that should be performed by specialists under appropriate sterile circumstances in which the rate of complications would be decreased. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…The most serious complication of circumcision is amputation of the penis or glans penis, with an inappropriate circumcision method the most significant cause (14). In a series of 6 patients with major circumcision complications such as excess circumcision, penile necrosis, and penile amputation, Ince et al reported that all patients were circumcised by circumcisers (15). Similarly, in the present study, 85.7% of the major complicated cases were circumcised by circumcisers.…”
Section: Discussionsupporting
confidence: 70%
“…The most serious complication of circumcision is amputation of the penis or glans penis, with an inappropriate circumcision method the most significant cause (14). In a series of 6 patients with major circumcision complications such as excess circumcision, penile necrosis, and penile amputation, Ince et al reported that all patients were circumcised by circumcisers (15). Similarly, in the present study, 85.7% of the major complicated cases were circumcised by circumcisers.…”
Section: Discussionsupporting
confidence: 70%
“…Several mechanisms may explain skin loss in the penile region following a circumcision. It can occur after direct excision during the major surgical procedure or following a postoperative skin infection or during postoperative debridement indicated for skin necrosis [21]. This loss of substance exposes the penis with subsequent major risk of infection and erectile dysfunction [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several reconstruction techniques are possible, they are functions of the extent of the loss of substance, ranging from directed healing to skin grafts using thin or thick flaps [21]; fasciocutaneous advancement flap using a flap from the inguinal, femoral [22] and even scrotal region. In the case presented, the authors opted for a skin advancement flap using the scrotal skin.…”
Section: Discussionmentioning
confidence: 99%
“…Amputation of the whole shaft of the penis after traditional ritual circumcision performed by a family member or unexperienced individual have been reported necessitating reconstructive expert in reimplantation. Untrained individuals who perform circumcisions are to be held responsible for the complications that arise and need to be stopped [11].…”
Section: Practitioner Experiencementioning
confidence: 99%
“…Although rare, traumatic complications of circumcisions have troubling consequences. Injury to the skin of the shaft [11,48], injury to the glans or urethra [49][50][51][52], or total amputation of the whole length of the phallus are reported [53,54]. These events, although very rare, are seen in rural regions where ritual mass circumcisions are performed by untrained individuals using primitive devices.…”
Section: Traumamentioning
confidence: 99%